Bridge management - Ryall, M.J (Elsevier Butterworth-Heinemann, 2010)
Comprehensive specialist information for the bridge engineer. Not only covers testing and assessment, but also financial and management issues. Highly illustrated with full colour diagrams and photographs As the emphasis in construction moves from building new bridges to maintenance and rehabilitation of existing stock, bridge management is becoming an increasingly important subject. This is the definitive, single volume reference for professionals and postgraduates, covering the whole gamut of bridge management topics. Highly illustrated and in full colour, this revised and updated second edition has been expanded to include new chapters on deterioration modelling, asset management and the impact of heavy goods vehicles. Including examples of practices and techniques drawn from around the world, this will be an invaluable source for the modern bridge engineer. Dr Michael J. Ryall has worked for over forty years, both in the UK and abroad, in the practice of design and construction of a wide variety of bridges. He has also taught and developed both undergraduate and postgraduate Bridge Engineering courses at the University of Surrey, and run bridge-related courses worldwide. Updated to focus on current practice and issues. Including the latest monitoring techniques, repair materials and life-cycle cost optimisation strategies. Full colour illustrations throughout.